Ride eaudiobook - Loveling, Daphne (Stone Kings MC, 2019)
TRIG Eva Van Buren. Ten years ago, I was this close to getting my hands on that tight little body. Now, she's my physical therapist. I've never forgotten her beauty: blonde hair, amazing sapphire eyes, toned legs . . . and the way she moves, every step turning me on. There's just one little problem with our unexpected reunion. She f*cking hates me. I don't care. Life has given me another shot and I'm not wasting it. While Eva works to get me back on my feet, I'll be doing everything possible to get her off of hers . . . and into my bed. EVA Trig Jackson. The most arrogant manwhore on the planet. I don't have time for men—but if I did, he'd be last on my list. I have to stay professional. Which isn't easy when his muscled, tattooed body makes me want to touch him all over . . . especially in places that have nothing to do with his treatment. He hurt me like no one ever has. I have to remember that, dig up the pain from where I buried it, and use it to keep him at bay. I can't trust him. So why do I want to rip his clothes off and give him the most intimate therapy possible? Contains mature themes.